Improving local government performance through benchmarking - Ammons, David N. (Routledge, 2025)
"Improving Local Government Performance Through Benchmarking sets the record straight on benchmarking and its value for performance improvement in local government. Benchmarking is a widely adopted public management reform of recent decades, yet it is often misunderstood by city and county governments; viewed too narrowly; or underappreciated by managers, elected officials, and students of local government for its potential as a tool. This book helps students of public administration and practitioners in local government-municipal and county government executives, department heads, program managers, and management analysts-to better understand the two major types of benchmarking in use by local governments in the US and beyond (metrics benchmarking and best practice benchmarking) and the promise and limitations of each type as tools of performance improvement. It lays out strategic decisions in the design and management of benchmarking projects, and highlights common errors to avoid - preparing managers and analysts for greater benchmarking success. Written in an easy-to-read style, this book will provide practical assistance to local government officials and students of public administration who aspire to become practitioners in the future"-- Provided by publisher.